PROSES MORFOLOGIS AFIKSASI DALAM KALIMAT (SINTAKSIS) DALAM BAHASA MANDAILING (BM) - Zainuddin Hasibuan (Multilingual, 2021)
The changes of affixation morphology have a number of effects on  the changes of sentence structure (syntax) in Mandailing language. The process of changes can also lead to a change in meaning directly. The objective of the research was to find out morphological change of affixes which  effected the changing of sentences structures (syntax) in Mandailing language. The method  which is used to carry out this research is qualitative research method. The type of research approach which is  used in this research is descriptive qualitative research, which is one type of qualitative research that uses a descriptive analysis process. Descriptive is intended to describe and get information about the data needed precisely. The data were collected by using observation and interview. The source of data in this research was taken from many informant of native speakers of Mandailing   language which had been  listened and interviewed by the researcher whether in the form of observation and interview. The research result of the research was finding many affixes in Mandailing language and three formula that was generally effected morphological change of affixes which was also effect the sentence structures and meaning of the sentences. They were ma + kt. dasar, ma + kt.dasar + i, ma + kt.dasar + kon/hon.